Associated Factors of Empathy Level Among Nurses in Tertiary Care Hospital Lahore: Factors Associated with Empathy Level in Nurses - Roger, Robinson; Sarwar, Hajra; Afzal, Muhammad (Pakistan Journal of Health Sciences, 2022)
It is well acknowledged that a high level of empathy among nurses is critical to their nursing care. For successful and efficient nursing care, empathy is a fundamental component of the nurse-patient relationship. Nurses are responsible to deliver patient-centered, safe, and effective nursing care at all levels of the health-care system. Nurses’ sympathetic role in the therapeutic setting begins with a thorough assessment of their patients’ bodily, psychological, and spiritual needs. Nurses’ capacity to listen empathetically to their patients and deliver empathic nursing care successfully leads to proper patient care, which increases patient satisfaction with nursing care. Objective: To determine the association of empathy levels with demographic factors among Nurses working at Public Tertiary care Hospitals Lahore. Methods: A cross sectional analytical study design was used to conduct this study. The Sample size of n=180 nurses were recruited through simple random sampling technique. Jefferson Empathy scale was used for data collection from participants to assess the empathy level among nurses. Filled questionnaires were collected and processed for data analysis through SPSS version 21. Results: The study findings stated that empathy level among nurses was not found in association with educational institute (p-value=.623), marital status (p-value-.771), education level (p-value=.556) and job experience (p-value=.395). It simply means that the mentioned demographic factors have no influence on nurses’ empathy level here in this study. Conclusion: It is concluded that the level of empathy among nurses was not found to be associated with the demographic factors of nurses like their age, experience and institute of graduation.